Unveiling the Determinants of Audit Completion Time in the Post-Pandemic Era: A Study of Manufacturing Companies Listed on the Indonesia Stock Exchange - Berlianto, Abiyuwara Wimba; Wulandari, Stepani Sisca; Akbar, Taufiq; Wijayanti, Inung (West Science Accounting and Finance, 2025)
This study seeks to analyze the impact of financial distress, company size, and Public Accounting Firm (PAF) size on audit reporting lag in manufacturing firms listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. The study employed a quantitative methodology utilizing panel data regression techniques, selecting 53 organizations chosen by purposive sampling. The investigation indicates that financial strain adversely impacts audit reporting lag, suggesting that increased financial pressure on a corporation correlates with an extended duration to finalize the audit. This discovery underscores the significant influence of a client's financial status on the promptness of audit reporting. Simultaneously, the size of the company and the size of the PAF exhibit no substantial influence on audit reporting latency, indicating that variations in operational scale or audit firm capability do not inherently affect the efficiency of the audit process. These findings provide empirical information to enhance the comprehension of the factors affecting timely audit reporting in the context of post-pandemic economic dynamics.